2021
DOI: 10.1186/s40168-021-01153-3
|View full text |Cite|
|
Sign up to set email alerts
|

Biogeographic traits of dimethyl sulfide and dimethylsulfoniopropionate cycling in polar oceans

Abstract: Background Dimethyl sulfide (DMS) is the dominant volatile organic sulfur in global oceans. The predominant source of oceanic DMS is the cleavage of dimethylsulfoniopropionate (DMSP), which can be produced by marine bacteria and phytoplankton. Polar oceans, which represent about one fifth of Earth’s surface, contribute significantly to the global oceanic DMS sea-air flux. However, a global overview of DMS and DMSP cycling in polar oceans is still lacking and the key genes and the microbial asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 108 publications
0
17
0
Order By: Relevance
“…These genes have been identified in diverse lineages of bacteria, including members of the SAR116 and Roseobacter clade ( Todd et al, 2011 , 2012 ; Choi et al, 2015 ), and, most recently, with the discovery of dddK in the SAR11 clade ( Sun et al, 2021 ). Of these genes, dddK has been reported as the most dominant in pelagic open water environments ( Teng et al, 2021 ), while the most abundant in productive coastal waters is the Roseobacter and SAR116-associated dddP ( Nowinski et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These genes have been identified in diverse lineages of bacteria, including members of the SAR116 and Roseobacter clade ( Todd et al, 2011 , 2012 ; Choi et al, 2015 ), and, most recently, with the discovery of dddK in the SAR11 clade ( Sun et al, 2021 ). Of these genes, dddK has been reported as the most dominant in pelagic open water environments ( Teng et al, 2021 ), while the most abundant in productive coastal waters is the Roseobacter and SAR116-associated dddP ( Nowinski et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%
“…DMS oxidation is performed by bacteria that possess one of three known enzymes, a multicomponent monooxygenase (DsoABCDEF), a DMS hydrogenase (DdhABC), and trimethylamine monooxygenase (Tmm) ( Horinouchi et al, 1999 ; McDevitt et al, 2002 ; Chen et al, 2011 ). The most abundant gene encoding bacterial DMS oxidation is tmm ( Teng et al, 2021 ), which requires methylamines to convert DMS to DMSO, is estimated to be found in 20% of all bacterial cells and is notably found in the SAR11 clade and Roseobacter group ( Chen et al, 2011 ; Lidbury et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the bacterial DMSP‐degrading genes such as dmdA and dddP have been carried out in varied marine environments (Cui et al ., 2015; Kuek et al ., 2016; Zeng et al ., 2016; Liu et al ., 2018; Nowinski et al ., 2019; Cui et al ., 2020; Teng et al ., 2021) and reported that these genes are taxonomically diverse and widespread across almost all major oceans, from tropical waters to the polar sea (Peng et al ., 2012; Cui et al ., 2015; Zeng et al ., 2016; Teng et al ., 2021). In comparison to DMSP catabolism, there were few molecular studies on environmental DMSP production and these showed bacterial DMSP production to be significant in surface coastal sediment, marine sediment and seawater, sea surface microlayer, estuary, and deep‐ocean environments (Williams et al ., 2019; Song et al ., 2020; Sun et al ., 2020; Zheng et al ., 2020; Sun et al ., 2021; Zhang et al ., 2021).…”
Section: Dmsp Biosynthesis and Catabolism In Different Oceanic Regionsmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the author reported that there is an error in one of the authors name. The name of the 8th co-author of this article should be “Guangfu Luo”, not “Guangfu Lu”.…”
mentioning
confidence: 99%